Prevalence and predictors of requests for facilitated child sexual exploitation on online platforms - Minihan, Savannah (Trends & issues in crime and criminal justice, 2024)
This study examines the prevalence of requests for facilitated child sexual exploitation (CSE) online. Of 4,011 Australians surveyed, 2.8 percent had received a request for facilitated CSE in the past year. Requests for facilitated CSE were significantly higher among those who had shared a photo of or information about children publicly online. Among respondents who had shared publicly, requests for facilitated CSE were significantly higher among men, younger individuals, linguistically diverse individuals, individuals with disability, and those who had experienced other sexual or violent harms online. The results highlight the need for increased awareness of the potential harms of posting photos of and information about children publicly online, and place onus on platforms to warn users of these potential harms.